HCV treatment barriers among HIV/HCV co-infected patients in the US: a qualitative study to understand low uptake among marginalized populations in the DAA era. (2nd May 2019) - Nápoles, Tessa M; Batchelder, Abigail W; Lin, Ada; Moran, Lissa; Johnson, Mallory O; Shumway, Martha; Luetkemeyer, Anne F; Peters, Marion G; Eagen, Kellene V; Riley, Elise D
ABSTRACT: Background: Well-tolerated, highly effective HCV treatment, known as direct-acting antivirals (DAAs), is now recommended for all people living with HCV, providing the tools for HCV elimination. We sought to understand treatment barriers among low-income HIV/HCV coinfected patients and providers with the goal of increasing uptake. Methods: In 2014, we conducted 26 interviews with HIV/HCV co-infected patients and providers from a San Francisco clinic serving underinsured and publically-insured persons to explore barriers impacting treatment engagement and completion. Interview transcripts were coded, and a thematic analysis was conducted to identify emerging patterns. Results: Conditions of poverty—specifically, meeting basic needs for food, shelter, and safety—undermined patient perceptions of self-efficacy to successfully complete HCV treatment programs. While patient participants expressed interest in HCV treatment, the perceived burden of taking daily medications without strong social support was an added challenge. This need for support contradicted provider assumptions that, due to the shorter-course regimens, support is unnecessary in the DAA era. Conclusions: Interferon-free treatments alone are not sufficient to overcome social-structural barriers to HCV treatment and care among low-income HIV/HCV co-infected patients. Support for patients with unmet social needs may facilitate treatment initiation and completion, particularly among those in challenging socioeconomic situations.